2015
DOI: 10.1016/j.bbrc.2015.07.073
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation of Argonaute-2 regulates RNA interference activity

Abstract: Post-translational modification of substrate proteins by small ubiquitin-like modifier (SUMO) regulates a vast array of cellular processes. SUMOylation occurs through three sequential enzymatic steps termed E1, E2 and E3. Substrate selection can be determined through interactions between the target protein and the SUMO E2 conjugating enzyme Ubc9 and specificity can be enhanced by substrate interactions with E3 ligase enzymes. We used the putative substrate recognition (PINIT) domain from the SUMO E3 PIAS3 as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
(35 reference statements)
2
11
0
Order By: Relevance
“…Previous studies have shown that human AGO2 gets SUMOylated at lysine 402 [77,78]. Consistent with this, we also found that the lysine residue 402, but not 266 or 693, of human AGO2 is modified by SUMO (Appendix Fig S3A).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that human AGO2 gets SUMOylated at lysine 402 [77,78]. Consistent with this, we also found that the lysine residue 402, but not 266 or 693, of human AGO2 is modified by SUMO (Appendix Fig S3A).…”
Section: Discussionsupporting
confidence: 90%
“…AGO2 acts as an efficient modulator in regulating miRNA processing, miRNA-guided gene silencing and other functions through various PTMs, including prolyl-4-hydroxylation [20, 21], phosphorylation [2226], ubiquitination [27, 33], polyADP-ribosylation [28] and SUMOylation [34]. Our study for the first time identified that AGO2 was acetylated.…”
Section: Discussionmentioning
confidence: 94%
“…We further explored the interaction properties with proteins of the four lncRNAs using CLIPdb and starBase V2.0 (Table 3). AGO2 can play a role of RNA interference by encoding a member of argonaute family of proteins [27] and it predictively interacted with TPT1-AS1 and MIR155HG. It is reported that AGO2 can regulate tumor invasion, proliferation, apoptosis and cell cycle in glioma, cervical and prostate cancer [2830].…”
Section: Discussionmentioning
confidence: 99%